PENGGUNAAN METODE KANO SEBAGAI ANALISIS E-SERVQUAL PADA WEBSITE WWW.SIAKADU.AC.ID (STUDI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA) - WIJAKSANA, MASTEREKA; SETYO IRIANI, SRI (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this study is whether the quality of the website is www.siakadu.unesa.ac.id already in accordance with the wishes of the students themselves or not as a form of customer satisfaction, which has an impact on universities to survive. This research is conclusive research. And using nonprobability sampling techniques. The sampling method used was snowball sampling with 210 respondents. Data retrieval techniques use questionnaires with closed statements and open questions. The measurement scale in this study used a Likert scale. The statistical analysis used was the Kano method using Ms.s program. Excel and IBM SPSS Statistics version 23. The results of this study indicate that all dimensions fall into the Indifferent category, the fulfillment of this attribute must be considered because its existence is questionable, whether this attribute is really a student need or not.